Development of Training Set for Pulse Circuit and Digital Technique Work, BD-1 Board, Vocational Level - Jubfun, Charn (Journal of the Association of Researchers, 2024)
This research aims 1) to study the satisfaction of students studying with the Pulse Circuit and Digital Technique Competency Training Kit, BD-1 board, used in teaching the Pulse Circuit and Digital Technique subject, course code 30105-1003, Higher Vocational Certificate Level, Year 1, Electronics Engineering Program, Prachinburi Technical College, Semester 1, Academic Year 2021, to have an efficiency according to the standard criteria of 80/80. A comparison of learning results before and after studying from a sample group of 28 people. The research tools included an achievement test and a satisfaction level questionnaire. Data were analyzed to find percentages (Percentage), means (Mean), standard deviations (Standard Deviation) and t-test statistics. The results of the analysis found that the level of experts' opinions on the Pulse Circuit and Digital Technique Competency Training Kit, BD-1 board The value is interpreted as being at the highest level. And the result of the analysis of the expert's opinion level on the pulse circuit and digital technique training kit, BD-1 board in the bag consists of 4 main parts in order. And the results of the learning process during learning and measuring the achievement after learning that was set at 80/80, Semester 1, Academic Year 2021, were equal to 82.25 / 80.18, which was found to be in line with the specified criteria. Semester 2, Academic Year 2022, had a value of 83.25 / 82.71, which was higher than the specified criteria. And Semester 1, Academic Year 2023, had a value of 83.90 / 82.67, which was higher than the specified criteria. Students who tested the competency through the test accounted for 100 percent. The results of the evaluation of the satisfaction level of experimental students who studied with the pulse circuit and digital technique training kit, BD-1 board, had a value that can be interpreted as being at a high level.